THE THERMODYNAMIC PROPERTIES OF MELTS OF DOUBLE SYSTEM MgO – Al2O3, MgO – SiO2, MgO – CaF2, Al2O3 – SiO2, Al2O3 – CaF2, SiO2 – CaF2 - Судавцова, В.; Гончаров, І.; Галініч, В.; Міщенко, Д.; Кудін, В.; Шевченко, М.; Шаркіна, Н. (Proceedings of National Aviation University, 2012)
Methodology of prognostication of thermodynamics properties of melts is presented from the coordinatesof liquidus of diagram of the state in area of equilibria a hard component is solution, on which energies ofmixing of Gibbs are expected in the double border systems of MgO – Al2O3, MgO – SiO2, MgO – CaF2,Al2O3 – SiO2, Al2O3 - CaF2, SiO2 - CaF2. For the areas of equilibrium there is quasibinary connection(MgAl2O4, Mg2SiO4, Al6Si2O13) – a grout at calculations was used equalization of Hauffe-Wagner. Theobtained data comport with literary